Pengaruh Industri dan Harga Lahan Terhadap Alih Fungsi Lahan Pertanian Sawah di Kabupaten Demak - Maulana, Faaruq; Widjonarko, Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2023)
Demand for built-up land will increase due to regional development, which is not directly proportional to the availability of land which does not change or increase. This raises several factors that have an impact on the environment, one of which is the widespread need for land for regional industrial development as a result of increasing economic growth and the continued development of an area. High demand for land will cause an increase in the value or price of land around the development area, one of which is paddy farming land. This study aims to measure the role of industrial development and increase in land prices on the conversion of paddy agricultural land. This research was conducted in Demak Regency, Central Java Province. This research was carried out with a quantitative approach using multiple linear regression by collecting data through document review and literature review related to the factors influencing the conversion of agricultural land functions such as industry and land prices. From the overall analysis, industrial development and an increase in land prices play a role or effect by 30.8% on the conversion of paddy fields in Demak Regency, while 69.2% are influenced by other variables outside the regression equation. Based on the results of this study, industrial development and increasing land prices have a less significant role or influence on the conversion of paddy fields in Demak Regency. This is because there are several other aspects that underlie the conversion of paddy fields in Demak Regency, such as economic, social and physical aspects of nature.